Parents Are Unaware of Their Youths' Tobacco Use: Results from the Population Assessment of Tobacco and Health Study. (4th May 2020) - King, Jessica L.; Merten, Julie W.; Nicksic, Nicole E.
ABSTRACT: BACKGROUND: In this study, we determined the prevalence of and factors associated with parent unawareness of youth tobacco use. METHODS: We used data from waves 1, 2, and 3 (2013‐2016) of the Population Assessment of Tobacco and Health study, a nationally representative study of 13, 650 US youth ages 12 to 17 and their parents. We conducted weighted multivariate analyses comparing parent unawareness of youth‐reported ever use and associations between parents' unawareness of youth use and covariates. RESULTS: Youth ever tobacco use ranged from 21.8% in 2013‐2014, to 24.1% in 2014‐2015, to 23.4% in 2015‐2016. Parent unawareness ranged from 57.6% in 2013‐2014, to 61.9% in 2014‐2015, and 64.5% in 2015‐2016. Factors associated with higher parent unawareness of youth tobacco use in 2015‐2016 were youth being female, black, or Hispanic (adjusted odds ratio [AOR] = 1.24‐2.61; all ps < .05). Youth with lower academic performance, relatives who used tobacco, tobacco available in the home, or past 30‐day use, were less likely to have parents unaware of their use (AORs 0.33‐0.56; all ps < .05). CONCLUSIONS: Among youth who reported ever using tobacco, most had parents who were unaware of their use. School‐based efforts targeting specific sociodemographic factors could increase parent awareness of youth tobacco use.